Bacterial and Fungal Dynamics During the Fermentation Process of Sesotho, a Traditional Beer of Southern Africa - Cason, Errol D.; Mahlomaholo, Bokang J.; Taole, Matšepo M.; Abong, George Ooko; Vermeulen, Jan-G; de Smidt, Olga; Vermeulen, Marcele; Steyn, Laurinda; Valverde, Angel; Viljoen, Bennie (Frontiers in Microbiology, 2020)
Sesotho is an indigenous cereal-based fermented drink traditionally produced in the mountain kingdom of Lesotho, Southern Africa. The present study sought to examine the microbial (bacterial and fungal) community composition of Sesotho at five fermentation stages in five different locations. Using culture-independent (Illumina sequencing) techniques it was found that the bacterial communities followed similar successional patterns during the fermentation processes, regardless of geographical location and recipe variation between breweries. The most abundant bacterial taxa belonged to the phyla Firmicutes (66.2 % of the reads on average) and Proteobacteria (22.1 %); the families Lactobacillaceae (54.9 %), Enterobacteriaceae (14.4 %) and Leoconostrocaceae (8.1 %); and the genera Lactobacillus (54 %), Leuconostoc (10.7 %), Leptotrichia (8.5 %) and Weissella (5.5 %). Most fungal taxa were from the phyla Ascomycota (60.7 %) and Mucoromycota (25.3 %); the families Rhizopodaceae (25.3 %), Nectriaceae (24.2 %), Saccharomycetaceae (16 %) and Aspergillaceae (6.7 %); and the genera Rhizopus (25.3 %), Saccharomyces (9.6 %) and Aspergillus (2.5 %). Lactic acid bacteria (LAB) such as Enterococcus, Pediococcus, Lactobacillus, Leuconostoc, and Wiesella; as well as yeasts belonging to the genus Saccharomyces, were dominant in all breweries during the production of Sesotho. Several pathogenic and food spoilage microorganisms (e.g., Escherichia, Shigella, Klebsiella, etc.) were also present, but the study demonstrated the safety potential of the Sesotho fermentation process, as these microbial groups decline throughout Sesotho production. The functional profiles of the different brewing steps showed that the process is dominated by chemoheterotrophic and fermentative metabolisms. This study reveals, for the first time, the complex microbial dynamics that occur during Sesotho production.